Nursery of red tilapia Oreochromis niloticus in a small-scale aquaponics system with different stocking densities - Hadiroseyani, Yani; May Sharly, Anita; Shafruddin, Dadang; Vinasyiam, Apriana (Jurnal Akuakultur Indonesia, 2023)
Aquaponics is a fish and hydroponic plant-rearing system that utilises fish waste as a plant nutrient. Because water quality can be maintained at an optimal level for fish in the system to enhance farming productivity. This study was conducted to evaluate the effects of fish density on the nursery stage of red tilapia in a small-scale aquaponic system. The study was conducted using a completely randomized design at three levels of stocking density, namely 250 fish/m2, 375 fish/m2, and 500 fish/m2 of red tilapia at an initial size of 6.8 ± 0.35 cm, with 30 net pots of bok choy plant as co-culture. The results that the increase in fish population escalated the productivity of both fish and vegetable in 30 days farming period. The stocking density did not affect fish survival 99 ± 0.82%, 97 ± 1.27%, and 97 ± 0.68%, respectively (p>0.05), but supported a better specific growth rate, namely 3.09 ± 0.30%/day; 3.57 ± 0.23%/day; 4.03 ± 0.04%/day (p<0.05). Interestingly, the smallest coefficient of diversity and lowest feed conversion ratio were obtained at 500 fish/m3, whereas absolute length growth did not differ. Bok choy production increased with fish density, namely 2.82 ± 0.06 kg; 2.88 ± 0.08 kg; 3.17 ± 0.10 kg, respectively (p<0.05). The water quality parameter values were almost identical in all treatments, except for the lowest bacterial abundance gained at stocking density of 500 fish/m3. In conclusion, the aquaponic system can be used to nurseries tilapia seeds at high stocking densities for production efficiency. Keywords: aquaculture, bok choy, hydroponics, intensification ABSTRAK Akuaponik adalah sistem pemeliharaan ikan dan tanaman hidroponik yang memanfaatkan kotoran ikan sebagai nutrisi tanaman. Karena kualitas air dapat dipertahankan pada tingkat optimal untuk ikan dalam sistem akuaponik untuk meningkatkan produktivitas budidaya. Penelitian ini dilakukan mengevaluasi pengaruh peningkatan kepadatan ikan pada tahap pendederan ikan nila merah dalam sistem akuaponik skala kecil. Penelitian dilakukan dengan menggunakan rancangan acak lengkap pada tiga tingkat kepadatan tebar yaitu 250 ekor/m2, 375 ikan/m2, dan ikan nila merah sebanyak 500 ekor/m2 dengan ukuran awal 6,8 ± 0,35 cm, pada masing-masing sistem aquaponik dengan 30 net pot tanaman bok choy. Hasil penelitian menunjukkan peningkatan populasi ikan telah meningkatkan produktivitas ikan dan sayuran dalam masa budidaya 30 hari. Peningkatan padat penebaran tidak berpengaruh terhadap kelangsungan hidup ikan yaitu berturut-turut sebesar 99 ± 0,82%, 97 ± 1,27%, dan 97 ± 0,68% (p>0,05), namun mampu mendukung laju pertumbuhan spesifik yang lebih baik yaitu 3,09 ± 0,30%/hari; 3,57 ± 0,23%/hari; dan 4,03 ± 0,04%/hari (p<0,05). Menariknya, koefisien keanekaragaman terkecil dan rasio konversi pakan terendah diperoleh pada kepadatan 500 ekor/m3, sedangkan pertumbuhan panjang absolut tidak berbeda. Produksi bok choy meningkat seiring dengan kepadatan ikan yaitu berturut-turut 2,82 ± 0,06 kg; 2,88 ± 0,08 kg; 3,17 ± 0,10 kg, (p<0,05). Nilai parameter kualitas air hampir sama pada semua perlakuan, kecuali kelimpahan bakteri terendah diperoleh pada padat tebar 500 ekor/m3. Secara keseluruhan, produksi ikan dan tanaman tertinggi terdapat pada kepadatan penebaran 500 ekor/m3. Kesimpulannya, sistem akuaponik dapat digunakan untuk pembibitan benih ikan nila dengan padat tebar tinggi untuk efisiensi produksi. Kata kunci: akuakultur, hidroponik, intensifikasi, pak coy